Lung Perfusion Assessment by Bedside Electrical Impedance Tomography in Critically Ill Patients - Xu, Mengru; He, Huaiwu; Long, Yun (Frontiers in Physiology, 2021)
As a portable, radiation-free imaging modality, electrical impedance tomography (EIT) technology has shown promise in bedside visual assessment of lung perfusion distribution in critically ill patients. The two main methods of EIT for assessing lung perfusion are the pulsatility method and the conductivity contrast (saline) bolus method. Increasing attention is being paid to the saline bolus EIT method in the evaluation of regional pulmonary perfusion in clinical practice. This paper seeks to provide an overview of experimental and clinical studies with the aim of clarifying the progress made in the use of the saline bolus EIT method. Animal studies revealed that the saline bolus EIT method presented good consistency with single photon emission computed tomography (SPECT) in the evaluation of lung regional perfusion changes in various pathological conditions. Moreover, the saline bolus EIT method has been applied to assess lung perfusion in pulmonary embolism and the effect of PEEP on regional V/Q and ARDS in several clinical studies. The implementation of saline boluses, data analysis, precision and cutoff values varied among different studies, and a consensus must be reached on the clinical application of the saline bolus EIT method. Further study is required to validate the impact of the described saline bolus EIT method on decision making, therapeutic management and outcomes in critically ill patients.